The influence of sports performance on economic-financial performance: An analysis of Brazilian soccer clubs from 2013 to 2017 - Gonçalves, Rafael Simão; Mendes, Renato Cruz; Henriques, Flávio Medeiros; Tavares, Gustavo Moreira (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This study examined the relationship between sports performance and economic-financial performance in the subsequent year based on the revenue sources of Brazilian sports clubs from 2013 to 2017. Sports performance was measured by the position in the national league and the overall team performance in all championships. To measure economic-financial performance, we used net revenue and other revenue sources, such as broadcasting, matchday, commercial, and player sales. Using panel data analysis, we found that team performance positively and significantly affects clubs’ economic-financial performance in the subsequent year. However, these effects were shown to be very heterogeneous when we compared different measures of team performance and types of revenue sources. The findings confirm the export market pattern in Brazil since the revenue from player sales was the variable most explained by previous sports performance.